Peningkatan Kinerja Karyawan melalui Motivasi Kerja dan Kompensasi pada PT Matahari Department Store Cabang Cibubur - Eigis Yani Pramularso (LPPM Universitas Trunojoyo Madura, 2021)
Work motivation and compensation are factors that are expected to maintain employee performance. With good work motivation and compensation, it is hoped that employees will always be sincere, have morale, and are happy to do their job. The purpose of this study was to determine the effect of work motivation factors and compensation factors on employee performance at PT Matahari Department Store Cibubur Branch. In this study, the population as well as the sample were all employees of the cashier, totaling 32 with data collection using a questionnaire with a five-level Likert scale. Methods of data analysis with multiple regression analysis with data processing techniques using SPPS version 25.0. This study shows that work motivation has a positive but insignificant effect on employee performance, compensation has a positive and significant impact on employee performance, and collectively, employee performance is influenced positively and significantly by work motivation and compensation. The correlation coefficient has a very strong relationship with the R value of 0.876, while the coefficient of determination has an R Square value of 0.767 so that the contribution of work motivation and compensation to employee performance is 76.7%, while the rest is by other factors such as competence and work environment. The conclusion is that employee performance can increase when work motivation and compensation also increase.